Optical generation of intense ultrashort magnetic pulses at the nanoscale - Tsiatmas, Anagnostis (2014)
Generating, controlling and sensing strong magnetic fields at ever shorter time and length scales is important for both fundamental solid-state physics and technological applications such as magnetic data recording. Here, we propose a scheme for producing strong ultrashort magnetic pulses localized at the nanoscale. We show that a bimetallic nanoring illuminated by femtosecond laser pulses responds with transient thermoelectric currents of picosecond duration, which in turn induce Tesla-scale magnetic fields in the ring cavity. Our method provides a practical way of generating intense nanoscale magnetic fields with great potential for materials characterization, terahertz radiation generation and data storage applications.